GOVERNMENT REGULATION NUMBER 24 OF 1997 CONCERNING LAND REGISTRATION IN IMPLEMENTATION AND PROBLEMS AT REGENCY/CITY NATIONAL LAND AGENCY OFFICES - Richard; Sudradjat, Agus (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Problems are complex and multi-functional and involve cross-sectoral aspects of life in society. Therefore, handling land problems cannot be seen from just one side, it must be comprehensive and integrated so that solutions can be resolved. In terms of community land registration, especially in Subang Regency, each agency related to land. This program is primarily concerned with issuing land certificates so that they can be fully functional and mobilized to take part in handling land issues in accordance with the scope of individual work. Coordination is carried out by the National Land Agency. This agency must have cooperation and a collaborative network with all related agencies and the need to handle strategic land issues, including land registration. This research uses normative juridical methods, with secondary data methods which are then analyzed using qualitative analysis techniques. The results show that the determination of land registration, especially in Subang Regency, if seen from Law Number 5 of 1960, is basically as intended in Article 46 to Article 72 of the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Implementing Regulations of Government Regulation Number 24 of 1997 concerning Land Registration. The sanctions given to land officials deviate from the legal provisions in registering land being handed over to the public. Even if there is evidence of a violation of fund allocation, it may be criminalized as an act of corruption.